Lifestyle-Induced Redox-Sensitive Alterations: Cross-Talk among the RAAS, Antioxidant/Inflammatory Status, and Hypertension. (25th October 2021) - Szabó, Renáta; Börzsei, Denise; Hoffmann, Alexandra; Lesi, Zelma Nadin; Gesztelyi, Rudolf; Juhász, Béla; Szebeni, Gábor J.; Osman, Jasmin; Sebestyén, Judith; Nagy, Arnold; Szegedi, Sándor; Varga, Csaba; et al.
Abstract : The development and progression of hypertension are closely linked to an unhealthy lifestyle; however, its underlying mechanisms are not fully elucidated. Our aim was to assess the effects of diet and exercise on the elements of the renin–angiotensin–aldosterone system (RAAS), redox-sensitive parameters, and the expression of the vascular tone regulator endothelial nitric oxide synthase (eNOS). Male control Wistar-Kyoto (WKY) and stroke-prone spontaneously hypertensive (SHRSP) rats were randomized based on the type of diet (standard chow, high-fat diet: HT, and fructose-enriched diet: HF) and exercise (voluntary wheel-running exercise or lack of exercise). After 12 weeks of experimental period, the concentrations of the RAAS elements, myeloperoxidase (MPO) activity, tumor necrosis factor alpha (TNF- α ) concentrations, levels of superoxide dismutase (SOD) and glutathione (GSH), and expressions of extracellular signal-regulated kinase1/2 (ERK1/2) and phosphorylated ERK1/2 as well as eNOS were measured in the cardiac tissue of WKY and SHRSP rats. We found that the RAAS elements were overactivated under hypertension and were further elevated by HT or HF diet, while HT and HF diet enhanced MPO and TNF- α parameters as well as the expression of pERK1/2; SOD, GSH, and eNOS levels were decreased. These changes occurred in WKKY rats and reached the statistically significant level in SHRSP animals. 12 weeks of exercise compensated the adverse effects of HT and HF via alleviating the concentrations of the RAAS elements and inflammatory markers as well as increasing of antioxidants. Our findings prove that SHRSP rats are more vulnerable to lifestyle changes. Both the type of diet and exercise, as a nonpharmacological therapeutic tool, can have a significant impact on the progression of hypertension.